Ethnomedical Knowledge of Plants Used in Nonconventional Medicine for Wound Healing in Lubumbashi, Haut-Katanga Province, DR Congo - Bashige Chiribagula Valentin; Okusa Ndjolo Philippe; Manya Mboni Henry; Bakari Amuri Salvius; Masengu Kabeya Suzanne; Félicien Mushagalusa Kasali; Lumbu Simbi Jean Baptiste (The Scientific World Journal)
Medicinal plants used for wound healing in Lubumbashi have yet to be discovered. Inventory or profile of their taxa has yet to be established. The present study was carried out to survey the plants used in traditional medicine in Lubumbashi to treat wounds and to define their ethnomedical characteristics. The study was conducted between March 2021 and August 2022, using semistructured interview surveys of households (n = 2730), herbalists (n = 48), and traditional practitioners: TPs (n = 128).The 2,906 interviewed (sex ratio M/F = 0.9; mean age: 56 ± 3 years; and experience: 17 ± 4 years) provided information on 166 taxa, 130 used against chronic wounds, among which Securidaca longepedunculata was the top cited. Most of these taxa are shrubs (33%), belonging to 48 botanical families dominated by the Fabaceae (16%). They are indicated in 70 other pathologies. From these 166 taxa, 198 healing recipes are obtained, 11 combining more than one plant. In all these recipes, the leaf (>36%) is the most used part, and the poultice (>36%) is the most popular form of use. Twelve taxa are cited for the first time as medicinal plants, of which Agelanthus zizyphifolius has the highest consensus and Erigeron sumatrensis has the highest usual value. For the various plants used to treat wounds, some of which are specific to the region, further studies should focus on validating this traditional use.